Critical Quality Control on Determination of Boron Using ICP-OES with Gravimetric Method - Robbika, Oktavia Isma; Rohyami, Yuli; Hadriansyah, Hendra (Indonesian Journal of Chemical Analysis (IJCA), 2022)
Critical quality control on the determination of boron using ICP-EOS with gravimetric method is carried out. This study was conducted to examine the critical aspects which include linearity, LOD, LOQ, precision, and accuracy. Based on the results of the study showed that the determination of boron with the ICP-OES method was following the critical aspects of quality control test results. The linearity of the calibration curve with a concentration range of 0 - 10 mg/L has linearity with a correlation coefficient of 0.9998 and a determination coefficient of 0.9996. The standard solution calibration curve follows the linear regression equation y = 2567.5 x + 23.043. This method has a LOD of 1.24 mg/L and a LOQ of 4.13 mg/L. The ICP-OES method has high precision and accuracy at low, medium, and high concentration levels. The testing precision of low, medium and high concentration levels is 0.44, 0.54, and 0.14%. The accuracy obtained for the three concentration levels was 98.03, 95.05, and 98.61%. Based on the ANOVA test, it was shown that the precision and accuracy at all concentration levels were not significantly different.